PENDUKUNGAN MASYARAKAT TERHADAP WARGANYA YANG BERPROFESI SEBAGAI PENCOPET DI KRL JABODETABEK (STUDI KASUS KAMPUNG X) - Steviana Steviana (Jurnal Kriminologi Indonesia, 2011)
This research aims to find out the causes and processes of society support for its member but this is not to support something positive like in general, but the supporting society of its member who works as pickpocket on Jabodetabek train. In an effort to get the results of research in accordance with its objectives, the researcher using qualitative research methods. This study set in a village on suburb of Depok. The results of this research is: First, pointed out that the perpetrators and residents in village x has low socio-economic characteristics as well as having a strong social cohesion. Second, the existence of the support provided by the society to the prepetrator in the form of letting, acceptance and protection. This happens through a support process in which the society that located in lower socio-economic form a cultural framework that is legal cynicism. Here we can also see that the perpetrator retains the values of kindness shown to their family and the society of X village.